The Effect of Training, Used-Hand, and Experience on Endoscopic Surgery Skills in an Educational Computer-Based Simulation Environment (ECE) for Endoneurosurgery Training. (December 2019) - Cagiltay, Nergiz Ercil; Ozcelik, Erol; Isikay, Ilkay; Hanalioglu, Sahin; Suslu, Ahmet E.; Yucel, Taskin; Berker, Mustafa
Today, virtual simulation environments create alternative hands-on practice opportunities for surgical training. In order to increase the potential benefits of such environments, it is critical to understand the factors that influence them. This study was conducted to determine the effects of training, used-hand, and experience, as well as the interactions between these variables, on endoscopic surgery skills in an educational computer-based surgical simulation environment. A 2-hour computer-based endoneurosurgery simulation training module was developed for this study. Thirty-one novice- and intermediate-level resident surgeons from the departments of neurosurgery and ear, nose, and throat participated in this experimental study. The results suggest that a 2-hour training during a 2-month period through computer-based simulation environment improves the surgical skills of the residents in both-hand tasks, which is necessary for endoscopic surgical procedures but not in dominant hand tasks. Based on the results of this study, it can be concluded that computer-based simulation environments potentially improve surgical skills; however, the scenarios for such training modules need to consider especially the bimanual coordination of hands and should be regularly adapted to the individual skill levels and progresses.